2021
DOI: 10.4103/jfmpc.jfmpc_70_21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and quality of life in primary caregiver of children with cerebral palsy

Abstract: Objective: Study the correlation of depression and quality of life (QoL) in primary caregivers (mothers) of children with cerebral palsy (CP). Methods: An observational cross-sectional study was conducted on a total of 203 primary caregivers (mothers) of children with CP. The depression and QoL in the caregivers were assessed using the Montgomery and Asberg Depression Rating Scale and World Health Organization Quality of Life Instrument (WHOQOL-BREF) (physical, psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
1
7
0
6
Order By: Relevance
“…Although the chronic condition affects the entire family, in general, the mother, as she is the one most involved in care, starts to live for her child, giving up her own life ( 19 ) . The maternal figure, as the main caregiver of children with special health care needs, was evidenced in numerous studies ( 18 - 23 ) , as well as the need for the main family caregiver to abandon employment ( 22 - 23 ) , intensifying social vulnerability, both due to financial disadvantage and the lack of socialization with other individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the chronic condition affects the entire family, in general, the mother, as she is the one most involved in care, starts to live for her child, giving up her own life ( 19 ) . The maternal figure, as the main caregiver of children with special health care needs, was evidenced in numerous studies ( 18 - 23 ) , as well as the need for the main family caregiver to abandon employment ( 22 - 23 ) , intensifying social vulnerability, both due to financial disadvantage and the lack of socialization with other individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudios han puesto de mani$esto cómo el nacimiento de un hijo con parálisis cerebral supone un cambio para la vida de los padres, con marcadas afectaciones en su salud física y emocional, la situación laboral y profesional, las relaciones familiares y sociales (Whittingham et al, 2011). En el cuidado de los hijos, los padres experimentan niveles de estrés mayores a los de la población general, con alta signi$cancia clínica traducida en ansiedad y en depresión, que requieren intervenciones cognitivas y clínicas (Ribeiro et al, 2014;Sonune et al, 2021;Tseng et al, 2016), lo que es potenciado por el cuestionamiento que otros hacen del cuidado ofrecido (Hagerman et al, 2022), lo que coincide con los relatos del presente estudio.…”
Section: Discussionunclassified
“…. Studies in the literature found that functional level association between lower quality of life (Sonune et al, 2021;Yilmaz et al, 2010). In a study conducted by Sonune et al, in which the relationship of depression and quality of life of mothers of children with cerebral palsy were examined with the functional level, it was found that the quality of life was significantly affected by the functional level (Sonune et al, 2021).…”
Section: Discussionmentioning
confidence: 99%